(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Blue Baby Syndrome, medically termed methemoglobinemia, is a clinical condition characterized by a bluish discoloration of an infant’s skin due to reduced oxygen-carrying capacity of blood. The disorder may be congenital or acquired. The acquired form is primarily associated with nitrate contamination in drinking water and food. Infants below one year of age are particularly vulnerable. The present study focuses on nitrateinduced methemoglobinemia in Pakur district, specifically in the Amrapara and Maheshpur blocks. Water samples collected from selected mining areas were analyzed to determine nitrate concentration and assess associated health risks. The findings indicate seasonal variations in nitrate levels, though values remain within permissible limits. Continuous monitoring and public awareness are nevertheless essential to prevent health hazards.